Synthetic targets as mechanistic probes for the key biosynthetic enzyme, dehydroquinate synthase : a dissertation submitted to Massey University in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Institute of Fundamental Sciences, Palmerston North - Negron, Leonardo (Massey University, 2009)
Dehydroquinate synthase (DHQS) catalyses the five-step transformation of the seven carbon sugar 3-deoxy-D-arabino-heptulosonate 7-phosphate (DAH7P) to the carbacycle dehydroquinate (DHQ). Multiple studies have described in detail the mechanism of most of the steps carried out by DHQS with the exception of the final cyclisation step. In this study, (3S)-3-fluoro-DAH7P and (3R)-3-fluoro-DAH7P (fluorinated analogues of DAH7P) were produced and assayed across three phylogenetically distinct sources of DHQS in order to determine the role of the enzyme during the cyclisation step of the reaction. Incubation of (3S)-3-fluoro-DAH7P with DHQS from Escherichia coli, Pyrococcus furiosus, and Kiwifruit resulted in the production of different ratios of (6S)-6-fluoro-DHQ and 1-epi-(6S)-6-fluoro-DHQ for each enzyme. In addition, enzyme catalysis showed a slowing of reaction rates when (3S)-3-fluoro-DAH7P was used, suggesting that the fluorine at C-3 is stabilising the enol pyranose. An increase in the stabilisation of the fluoro-enol pyranose would allow release of this substrate intermediate from the enzyme to compete with the on-going on-enzyme reaction. The differences in the ratio of products formed suggest that the cyclisation occurs in part on the enzyme and that the epimeric product arises only by an abortive reaction pathway where the (3S)-3-fluoro-enol pyranose is prematurely released and allowed to cyclise free in solution. Once in solution, the (3S)-3-fluoro-enol pyranose could undergo a conformational change in the ring leading to the formation of the epimeric product. Furthermore, it is suspected that the position of fluorine influences the likely transition-state in carbacycle formation leading to the production of the epimeric product. This research has illuminated the role of the enzyme in guiding the correct stereochemistry of the product and illustrates the important molecular interplay between the enzyme and substrate.
Keywords: Antimicrobials; Bacterial enzymes; Enzyme reaction; Lyases; Fields of Research::250000 Chemical Sciences::250100 Physical Chemistry (Incl. Structural)::250106 Mechanisms of Reactions